Feasibility and acceptability of home-based HIV testing among refugees: a pilot study in Nakivale refugee settlement in southwestern Uganda - O’Laughlin, Kelli N.; He, Wei; Greenwald, Kelsy E.; Kasozi, Julius; Chang, Yuchiao; Mulogo, Edgar Mugema; Faustin, Zikama M.; Njogu, Patterson; Walensky, Rochelle P.; Bassett, Ingrid V. (BMC Infectious Diseases, 2018)
Background: Refugees in sub-Saharan Africa face both the risk of HIV infection and barriers to HIV testing. We conducted a pilot study to determine the feasibility and acceptability of home-based HIV testing in Nakivale Refugee Settlement in Uganda and to compare home-based and clinic-based testing participants in Nakivale. Methods: From February–March 2014, we visited homes in 3 villages in Nakivale up to 3 times and offered HIV testing. We enrolled adults who spoke English, Kiswahili, Kinyarwanda, or Runyankore; some were refugees and some Ugandan nationals. We surveyed them about their socio-demographic characteristics. We evaluated the proportion of individual’s encountered (feasibility) and assessed participation in HIV testing among those encountered (acceptability). We compared characteristics of home-based and clinic-based testers (from a prior study in Nakivale) using Wilcoxon rank sum and Pearson’s chi-square tests. We examined the relationship between a limited number of factors (time of visit, sex, and number of individuals at home) on willingness to test, using logistic regression models with the generalized estimating equations approach to account for clustering. Results: Of 566 adults living in 319 homes, we encountered 507 (feasibility = 90%): 353 (62%) were present at visit one, 127 (22%) additional people at visit two, and 27 (5%) additional people at visit three. Home-based HIV testing participants totaled 378 (acceptability = 75%). Compared to clinic-based testers, home-based testers were older (median age 30 [IQR 24–40] vs 28 [IQR 22–37], p < 0.001), more likely refugee than Ugandan national (93% vs 79%, < 0.001), and more likely to live ≥1 h from clinic (74% vs 52%, < 0.001). The HIV prevalence was lower, but not significantly, in home-based compared to clinic-based testing participants (1.9 vs 3.4% respectively, p = 0.27). Testing was not associated with time of visit (p = 0.50) or sex (p = 0.66), but for each additional person at home, the odds of accepting HIV testing increased by over 50% (OR 1.52, 95%CI 1.12–2.06, p = 0.007). Conclusions: Home-based HIV testing in Nakivale Refugee Settlement was feasible, with 90% of eligible individuals encountered within 3 visits, and acceptable with 75% willing to test for HIV, with a yield of nearly 2% individuals tested identified as HIV-positive.
Keywords: HIV testing; Home-based HIV testing; Refugees; Uganda; Displaced population; Humanitarian; HIV